All pride, no ego : a queer executive's journey to living and leading authentically - Fielding, Jim (James D.) (John Wiley & Sons, Inc., 2023)
"This is an inspirational leadership story told from the vantage point of an LGBTQ+ individual. It will highlight Fielding's journey and career starting in blue-collar Toledo, Ohio at a c-suite level position in retail and media/entertainment. This is a book to inspire authentic, servant leadership and to encourage people to own their truth to bring out the best in themselves and their teams. Fielding will use his personal story to illustrate key decisions and inflexion points ("Moments of Truth") that highlight his style, learnings, successes, and failures. Jim wants it to speak to everyone who has struggled with finding their personal leadership style, but especially to the Queer young people who feel marginalized, misunderstood, and held back from their path. It is a journey about finding and loving yourself....and using that strength to make the world a better place"--